Reducing teachers' marking workload and developing pupils' learning : how to create more impact with less marking - Richards, Gill; Richardson, Rhian (London ; New York : Routledge, Taylor & Francis Group, 2020)
"Based on a ground-breaking Department of Education-funded project and written by experienced teachers and educational practitioners, Reducing Teachers' Marking Workload and Developing Pupils' Learning shares strategies for reducing marking workload without compromising the quality of feedback pupils receive. This book presents a range of marking strategies, describing the process of trialling, testing and evaluating the impact which is relevant to any classroom. The strategies included in this book, proven to be immediately effective in schools, include: Advice on how to ensure feedback is meaningful for pupils The benefits of self-assessment and developing this in the classroom Marking for individuals, groups, and whole classes Written for teachers by teachers, Reducing Teachers' Marking Workload and Developing Pupils' Learning is a valuable resource for teachers, educators and student teachers looking to develop their professional practice, demystify education research, and make the impact of their marking and feedback hugely more effective"--
Includes bibliographical references and index.
Keywords: Grading and marking (Students); Educational tests and measurements